Driving Organic Nanocrystals Dissolution Through Electrochemistry. Issue 8 (5th August 2021) - Bussetti, Gianlorenzo; Filoni, Claudia; Li Bassi, Andrea; Bossi, Alberto; Campione, Marcello; Orbelli Biroli, Alessio; Castiglioni, Chiara; Trabattoni, Silvia; De Rosa, Stefania; Tortora, Luca; Ciccacci, Franco; Duò, Lamberto
Abstract: We have recently discussed how organic nanocrystal dissolution appears in different morphologies and the role of the solution pH in the crystal detriment process. We also highlighted the role of the local molecular chemistry in porphyrin nanocrystals having comparable structures: in water‐based acid solutions, protonation of free‐base porphyrin molecules is the driving force for crystal dissolution, whereas metal (Zn II ) porphyrin nanocrystals remain unperturbed. However, all porphyrin types, having an electron rich π‐structure, can be electrochemically oxidized. In this scenario, a key question is: does electrochemistry represent a viable strategy to drive the dissolution of both free‐base and metal porphyrin nanocrystals? In this work, by exploiting electrochemical atomic force microscopy (EC‐AFM), we monitor in situ and in real time the dissolution of both free‐base and metal porphyrin nanocrystals, as soon as molecules reach the oxidation potential, showing different regimes according to the applied EC potential. Abstract : Free‐base porphyrin (P) nanocrystals can be dissolved in acid electrolytes only when the second porphyrin oxidation is reached. Indeed, molecules only show a surface‐pit enhancement after the first oxidation. In addition, metal‐Ps, which are stable when immersed in acids, can be dissolved if their oxidation electrochemical potential is applied. These occurrences prove that molecule oxidation is the driving mechanism of crystal dissolution.